Analysis and Application of Construction Management in The Waled-Ciledug BTS Road Reconstruction Project - Radja Syahidir Firdaus; Herry Hermawan (CV. Syntax Corporation Indonesia, 2025)
Project planning, cost, time, quality, contract administration, and safety management are the regulated aspects of construction in construction management. As a result, project objectives cannot be realized without competent construction management. Planning, execution, and control are the three main functions of construction management. All human and other project resources are managed through these three processes: planning, execution, and review. The purpose of this study aims to determine construction time management, find out how long the project duration will take if using CPM and PERT methods, analyze CPM and PERT on the comparison of planning time. The approach method used is a qualitative technique that involves collecting field data that will be used as information for the research topic. The researcher uses the CPM and PERT methods as a tool in projects related to a management in planning and control in the project. The CPM and PERT methods are used to figure out the duration of the project required and also identify the types of critical work in the project. Based on the analysis conducted, the CPM method only requires 100 days and the PERT method 100.48 days. Using the CPM method produces a time efficiency of up to 20 days compared to the PERT method of only 19.52 days. From the results obtained, the critical path of the two methods is A, B, C, D, and also the non-critical path is E, the duration is faster than the previous plan schedule which is 120 days.